Efectos de los conservantes naturales ɛ-polilisina y propóleo en la vida útil del queso fresco pasteurizado - Cedeño Medranda, Karen Abigail (2022)
The objective of this work was to evaluate the effects of the natural preservatives ε-Polylysine and Propolis on the shelf life of fresh pasteurized cheese, being an experimental investigation, a completely randomized block design (DBCA) was applied, with 6 treatments and 4 repetitions, obtaining a total of 24 experimental units, the behavior of the preservatives on acidity, pH, molds and yeasts, as well as the kinetic behavior of the cheese stored at a temperature of 4 °C for 55 days, was evaluated. Through microbiological analysis, the presence of molds and yeasts was detected from day 30 for all treatments, which may have been associated with the preservatives used. It is necessary to mention that the counts reported on day 55 in the treatments with the preservative Propolis (TP1, TP2 and TP3) are below the allowed count that cause health risks (500 PU/g) established in the Mexican standards NMX-F-092:1970, which is very good. While in the Ɛ-Polylysine treatments (TE1, TE2 and TE3) there were high presences of propagating units (PU) of molds and yeasts, allowed by the standard. The sensory analysis (hedonic scale) was performed on 75 untrained tasters and the results were analyzed using the non-parametric Kruskal Wallis test, where significant statistical differences were identified between the attributes of the treatments by the panelists, thus suggesting the rejection of the null hypothesis.